Appropriate aggregation is needed for highly active Pt/Al2O3 to enable hydrogenation of chlorinated nitrobenzene. Issue 55 (17th June 2022) - Gu, Rongtian; Meng, Deming; She, Minyi; Wang, Yibo; Yang, Hua; Guo, Xiangke; Xue, Nianhua; Ding, Weiping
Abstract : Access to aggregated Pt particles on the non-reducing support Al2 O3 is essential for selective hydrogenation of chlorinated nitrobenzene to aniline chloride, whereas atomic platinum is nearly inactive. Abstract : The atomic dispersion of a noble metal with a reducible support has been reported to be beneficial for catalytic hydrogenation reactions. Conversely, we found that Pt particles (3–5 nm) could be obtained on the non-reducible support Al2 O3 by weakening the interaction between the metal and support using oleic acid, and the turnover frequency of catalyzing the hydrogenation of chlorinated nitrobenzene could reach 3700 h −1, which is three orders of magnitude higher than that of atomic platinum species.